2022
DOI: 10.1186/s12864-022-08923-9
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA lncMYOZ2 mediates an AHCY/MYOZ2 axis to promote adipogenic differentiation in porcine preadipocytes

Abstract: Long non-coding RNAs (lncRNAs) play a vital role in regulating adipogenesis. However, the associated regulatory mechanisms have yet to be described in detail in pig. In this study, we demonstrate a critical role for lncMYOZ2 in adipogenesis from porcine preadipocytes. Specifically, lncMYOZ2 was more abundant in the adipose tissue of Mashen (fat-type) pigs than for Large White (lean-type) pigs, and knockdown of this lncRNA significantly inhibited the differentiation of porcine preadipocytes into adipocytes. Mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Numerous studies have linked various lncRNAs to preadipocyte differentiation and adipogenesis, highlighting the role of altered lncRNA expression in the development and progression of obesity [38,39]. The lncMYOZ2 mediates an AHCY/MYOZ2 axis to promote adipogenic differentiation in porcine preadipocytes [40]. Our study also revealed that the overexpression of MSTRG4710 upregulated PPARγ, C/EBPα gene expression, along with an increase in the number of lipid droplets.…”
Section: Discussionsupporting
confidence: 56%
“…Numerous studies have linked various lncRNAs to preadipocyte differentiation and adipogenesis, highlighting the role of altered lncRNA expression in the development and progression of obesity [38,39]. The lncMYOZ2 mediates an AHCY/MYOZ2 axis to promote adipogenic differentiation in porcine preadipocytes [40]. Our study also revealed that the overexpression of MSTRG4710 upregulated PPARγ, C/EBPα gene expression, along with an increase in the number of lipid droplets.…”
Section: Discussionsupporting
confidence: 56%
“…Interestingly, genomic methylation changes due to knockdown or overexpression of AHCY in HeLa cells are associated with the up or downregulation of genes involved in metabolic pathways, such as the peroxisome proliferator-activated receptor ( PPAR ) pathway [ 11 ], which includes PPARG , the master regulator of adipocyte differentiation [ 12 ]. One recent study also suggested that a long non-coding RNA, presumably involved in the modulation of AHCY , alters cellular methylation patterns and affects regulation of adipogenesis in porcine preadipocytes [ 13 ].…”
Section: Introductionmentioning
confidence: 99%